Semantic, Pragmatic, and Legal Analysis of "Washing Overboard" in Marine Contracts: Implications of Translations and Causal Implications" - Himpun Panggabean (Edelweiss : Journal Of Innovation In Educational Research, 2026)
Abstract This paper presents an academic linguistic analysis of the term washing overboard in English marine insurance contracts, highlighting its semantic, pragmatic, and legal dimensions. The study examines how the Indonesian translation “tersapu ombak” narrows the original meaning, potentially undermining the protective intent of the contract for the insured. Using a combination of linguistic analysis, translation theory, and legal principles, the paper demonstrates that semantic narrowing, misguided translation, and a focus on direct evidence have led insurers to deny claims improperly, disregarding the broader causal context recognized in maritime law and industry practice. The analysis incorporates prima causa and proxima causa, showing that multiple causal factors—including natural perils such as storms, rough seas, and wind—contribute to cargo loss. The principle of contra proferentem is applied to argue that contractual ambiguities must be resolved in favor of the insured. Additionally, this study reviews authoritative sources, including Institute Cargo Clauses (ICC A/B/C), maritime dictionaries, and standard insurance texts, to support a comprehensive understanding of washing overboard. Ethical considerations in data analysis and the role of translation fidelity are emphasized, given that insured parties often cannot access or fully interpret source-language contracts. This paper provides recommendations for insurers, translators, legal practitioners, and policyholders to ensure that maritime insurance contracts maintain their protective and functional intent across languages.